THE ROLE OF THE VILLAGE GOVERNMENT IN IMPROVING THE QUALITY OF COMMUNITY PUBLIC SERVICESAT AT THE BALUGLOR VILAGE HEADE’S OFFICE - Siti Alfiyah (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Contains Basically service can not be separated from people's lives. The community always demands quality services from the government, even though these demands often do not meet expectations because people tend to think that government services are difficult, time-consuming and paid for. From this statement the author can formulate the problem as follows: What is the role of the village government in improving public services to the community at the Balung Lor Village Office? The method used in this analysis uses a descriptive method, which is carried out directly to the object of the problem, namely the Quality of Public Service to the Community at the Balung Lor Village Office. In general it can be explained that the quality of public services can be measured through 5 dimensions namely: 1) The Tangiable dimension is quite good because for the convenience of the place, the appearance of the employees, the ease of managing files, only in the disciplinary indicators there needs to be an evaluation. 2) The Reliability Dimension, in terms of accuracy, clarity, ability and expertise of employees is very good, has no problems or complaints from the public. 3) The Responsiveness dimension is still quite low because there are employees who are less responsive to community need. 4) The Assurance dimension, the quality of service is very good because it provides timely guarantees while providing services to the community. 5) The Emphaty dimension, excellent service quality, employee friendliness and non-discrimination in service proves that employees really appreciate all of society and employees prioritize the interests of customers or the community rather than personal interests and this is recognized and felt by the community.